2018
DOI: 10.1155/2018/9721730
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of TATB/VitonA Nanocomposites

Abstract: Nano-TATB particles were prepared by an ultrasonic-assisted spray method. Molecular dynamics simulation was used to select the best binder-VitonA. Then, using VitonA as a binder, TATB/VitonA nanocomposites were prepared by a compressed air spray evaporation method and the formation mechanism of TATB/VitonA nanocomposites was proposed. Meanwhile, the crystal morphology, particle size, crystal structure, thermal decomposition properties, and impact sensitivity properties of the raw materials of TATB, the prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Klaumunzer [7] and Jiang [8] recrystallized RDX and HMX, respectively, improving crystal quality and showing desensitization against stimuli from impact. It is not difficult to see that these two steps are usually carried out separately in existing studies [9][10][11][12][13][14]. However, the improvement of crystal quality by recrystallization does not necessarily have the effect of desensitization, and simply coating insensitive materials is often accompanied by a large loss of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Klaumunzer [7] and Jiang [8] recrystallized RDX and HMX, respectively, improving crystal quality and showing desensitization against stimuli from impact. It is not difficult to see that these two steps are usually carried out separately in existing studies [9][10][11][12][13][14]. However, the improvement of crystal quality by recrystallization does not necessarily have the effect of desensitization, and simply coating insensitive materials is often accompanied by a large loss of energy.…”
Section: Introductionmentioning
confidence: 99%
“…If the warhead of AGM-114 N was not perfectly cylindrical, it would be almost impossible to load. Compositions based on exotic reducing agents like boron, nanomaterials or core-shell particles have also been studied, but for now, they remain laboratory curiosity without practical use [1,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that CL-20 in the nanocomposite took the form of an α polymorph, and the nanocomposite had much lower sensitivity. Xu et al [15] prepared nano-TATB particles by ultrasonic-assisted spray method and used molecular dynamics simulation to select the best binder VitonA. The composite particles had higher thermal stability and lower mechanical sensitivity.…”
Section: Introductionmentioning
confidence: 99%